PENGASUHAN ANAK USIA DINI DI ERA TEHNOLOGI DIGITAL - Amita Diananda (stit-islamic-village, 2022)
Digital technology, such as gadgets (hardware) and their applications (software), has been able to change the world order in interacting and communicating. In the process of parenting early childhood, the use of gadgets is nothing unfamiliar. However, the use of gadgets, without control, in parenting, can make children experience a change in mental and attitude where gadgets begin to dwindle the attachment of children's relationships to parents and switches it into the attachment to gadgets. The use of digital technology for early childhood at home and school has increased in intensity, especially during the Covid-19 outbreak. The teaching and learning process in schools has changed from face-to-face meetings (offline) to long distance meetings (online). The purpose of this study is to anticipate early childhood from being addicted to gadgets, and parental control is needed then, mainly in controlling the duration of the use of the gadget devices and the selection of the content in the form of pictures/videos that the children watch. The task of parents is to be a controller in the transfer process of knowledge, values, and guidance. Thus the mental and psychological health and moral of children are well maintained. The results of this literature research show that